Are aluminium potroom workers at increased risk of neurological disorders?. Issue 4 (April 1997) - Sim, M; Dick, R; Russo, J; Bernard, B; Grubb, P; Krieg, E; Mueller, C; McCammon, C
Abstract : OBJECTIVE: To determine whether long term potroom workers in an aluminium smelter are at increased risk of neurological disorders. METHODS: Cross sectional study of 63 current and former aluminium potroom workers first employed before 1970 and with at least 10 years of service. A group of 37 cast house and carbon plant workers with similar durations of employment and starting dates in the same smelter were used as controls. The prevalence of neurological symptoms was ascertained by questionnaire. Objective tests of tremor in both upper and lower limbs, postural stability, reaction time, and vocabulary were conducted. All subjects were examined by a neurologist. RESULTS: No significant differences in age, race, or education were found between the two groups. Although the potroom group had higher prevalences for all but one of the neurological symptoms, only three odds ratios (ORs) were significantly increased; for incoordination (OR 10.6), difficulty buttoning (OR 6.2), and depression (OR 6.2). Tests of arm or hand and leg tremor in both the visible and non-visible frequencies did not show any significant differences between the two groups. Testing of postural stability showed no definitive pattern of neurologically meaningful differences between the groups. There were no significant differences between the two groups in reaction time, vocabulary score, or clinical neurological assessment. CONCLUSIONS: The objective measures of neurological function provided little support for the finding of increased neurological symptom prevalences in the potroom workers, although increased symptoms may be an indicator of early, subtle neurological changes. The results provide no firm basis for concluding that neurological effects among long term potroom workers are related to the working environment, in particular aluminium exposure, in potrooms. These findings should be treated with caution due to the low participation of former workers and the possibility of information bias in the potroom group.